Diatom-inferred salinity records from the Arctic Siberian Margin: Implications for fluvial runoff patterns during the Holocene. - Bauch, Henning A; Polyakova, Ye I (PANGAEA, 2003)
Diatom assemblages were employed to study temporal changes of Siberian river runoff on the Laptev Sea shelf. Using a correlation between freshwater diatoms (%) in core-top sediments and summer surface water salinities from the inner Kara Sea, salinity conditions were reconstructed for a site northeast of the Lena River Delta (present water depth 32 m) since 9 calendar years (cal) ka. The reconstruction indicate a strong, near-coastal, and river-influenced environment at the site until about 8.6 cal ka. Corroborated by comparison with other proxy records from further to the east, surface salinities increased from 9 to 14 until about 7.4 cal ka, owing to ongoing global sea level rise and synchronous southward shift of the coastline. Although riverine water became less influential at the site since then, salinities still varied between 12.5 and 15, particularly during the last 3.5 kyr. These more recent salinity fluctuations agree well with reconstructions from just north of the Lena Delta, emphasizing the strong linkage between shelf hydrography and riverine discharge patterns in Arctic Siberia.
(Table 1) Age determination of sediment core PS51/092-12
Keywords: Age, 14C AMS; Age, 14C calibrated, CALIB 4.3 (Stuiver et al., 1998); Age, dated; Age, dated material; Age, dated standard deviation; ARK-XIV/1b; Calendar age; DEPTH, sediment/rock; KAL; Kasten corer; Laboratory code/label; Laptev Sea; Polarstern; PS51/092-12; PS51 Transdrift-V